A new multivariate generalized log-double exponential family of distribution of kind-1. Issue 3 (4th May 2018) - David Sam Jayakumar, G. S.; Solairaju, A.; Sulthan, A.
Abstract: In this paper the authors propose a multivariate generalized log-double exponential family of distribution of kind-1. The proposed distribution is sarmanov type, the various important function and its special cases are also derived and discussed in the subsequent sections. Three parameters such as location, scale and shape determines the distributions and making changes to this results in emerge for subclasses of proposed distribution.